2010
DOI: 10.1113/jphysiol.2010.186965
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory role of hyperaemia and shear stress in microvascular adaptation to repeated heating in humans

Abstract: The endothelium, a single layer of cells lining the entire circulatory system, plays a key role in maintaining vascular health. Endothelial dysfunction independently predicts cardiovascular events and improvement in endothelial function is associated with decreased vascular risk. Previous studies have suggested that exercise training improves endothelial function in macrovessels, a benefit mediated via repeated episodic increases in shear stress. However, less is known of the effects of shear stress modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 21 publications
5
101
4
Order By: Relevance
“…It appears that the brachial artery became somewhat hyperresponsive following heat training, as shear AUC decreased in the presence of maintained FMD and increased ischemic handgrip responses. These findings contrast somewhat with the impact of exercise training on shearmediated dilator responses, and the explanation is not entirely clear, but it may be that heat training has less impact on resistance vessel remodeling than exercise training, even if it does modulate cutaneous microvascular function (8).…”
Section: Discussioncontrasting
confidence: 52%
“…It appears that the brachial artery became somewhat hyperresponsive following heat training, as shear AUC decreased in the presence of maintained FMD and increased ischemic handgrip responses. These findings contrast somewhat with the impact of exercise training on shearmediated dilator responses, and the explanation is not entirely clear, but it may be that heat training has less impact on resistance vessel remodeling than exercise training, even if it does modulate cutaneous microvascular function (8).…”
Section: Discussioncontrasting
confidence: 52%
“…Previous work has demonstrated that repeated increases in shear represent an important stimulus for vascular adaptations in function and structure (Green et al 2004;Tinken et al 2010). The perception that vascular adaptations are mediated by shear-stress-dependent mechanisms is well supported by both in vivo animal models and human experiments (Hambrecht et al 2003;McAllister et al 2005;Green et al 2010). In addition, repeated exposure to short periods of hypoxia (or ischaemia) may also contribute to cardiac and vascular adaptations (Laughlin et al 2008;Newcomer et al 2011).…”
Section: H J Thijssen and Othersmentioning
confidence: 98%
“…Several studies have explored the impact of repeated exposure to elevations in antegrade shear stress via training, heating, or in vitro manipulation of antegrade shear 7, 13, 14, 15, 16, 17. These studies consistently report a dose‐dependent increase in arterial caliber and improvement in endothelial function, possibly through upregulation of endothelial nitric oxide synthase 1, 18.…”
Section: Introductionmentioning
confidence: 99%